Relationship Between The Dynamics of Plankton Community Abundance, Total Organic Matter, and Salinity in Intensive Shrimp Farming Systems - Munjayana, Munjayana; Ekasari, Julie; Utari, Heny Budi; Wiyoto, Wiyoto; Vinasyiam, Apriana; Mubarak, Ahmad Shofy (Department of Aquaculture, 2024)
Plankton plays an important role in shrimp cultivation in ponds, both as an indicator of water quality and as a natural food source for shrimp that are raised. The purpose of this study was to measure the relationship between the dynamics of the plankton community, the concentration of total organic matter, and water salinity with the abundance of plankton in intensive shrimp farming systems. The study was conducted on six units of ponds located in Cirebon district, West Java, Indonesia. The ponds were lined with HDPE on each side and plastic mulch at the bottom. Post larvae of shrimp were stocked at an average density of 110 shrimp.m-2 and maintained for 98 days. Water quality samples were collected for daily measurement. Data were analyzed descriptively and then analyzed using Pearson's correlation test and regression. The results of this study showed that during the shrimp rearing period, 65 species of plankton were identified, consisting of Chlorophyta 20%, Cyanophyta 15.38%, Diatoms 26.15%, Euglenophyta 6.15%, Dinoflagellates 4.62%, Protozoa 10.77%, and Ciliates 16.92% with an average density ranging from 7.56x105-19.99x105 cells.mL-1. Chlorella sp. (Chlorophyta) and Oscillatoria sp. (Cyanophyta) were found to be the dominating species in all ponds. Total phytoplankton density tended to be higher during the first 54 days of culture. The results of the correlation and regression tests showed that the composition of plankton, the concentration of total organic matter, and the salinity of the water affected the abundance of plankton in the pond.